Vulnerability to Stress and Coping Strategies among Undergraduate Students in Baghdad City - Mohammed Baqer Habeeb (Kufa Journal for Nursing Sciences)
Objective: The study aims to determine the level of vulnerability to stress perceived by students and the sources of stress, identify strategies do students frequently use to relieve their stress, and find out the association between study variables and vulnerability to stress.